Testing for variation in photoperiodic plasticity in a butterfly: Inconsistent effects of circadian genes between geographic scales - Olle Lindestad; Sören Nylin; Christopher W. Wheat; Karl Gotthard (Ecology and Evolution, 2024)
Abstract The genetic components of the circadian clock have been implicated as involved in photoperiodic regulation of winter diapause across various insect groups, thereby contributing to adaptation to adverse seasonal conditions. So far, the effects of within‐population variation in these genes have not been well explored. Here, we present an experimental test of the effects of within‐population variation at two circadian genes, timeless and period, on photoperiodic responses in the butterfly Pararge aegeria. While nonsynonymous candidate SNPs in both of these genes have previously shown to be associated with diapause induction on a between‐population level, in the present experiment no such effect was found on a within‐population level. In trying to reconcile these results, we examine sequence data, revealing considerable, previously unknown protein‐level variation at both timeless and period across Scandinavian populations, including variants unique to the population studied here. Hence, we hypothesize that these variants may counteract the previously observed diapause‐averting effect of the candidate SNPs, possibly explaining the difference in results between the experiments. Whatever the cause, these results highlight how the effects of candidate SNPs may sometimes vary across genetic backgrounds, which complicates evolutionary interpretations of geographic patterns of genetic variation.